Detection of myocardial medium‐chain fatty acid oxidation and tricarboxylic acid cycle activity with hyperpolarized [1–13C]octanoate. (6th January 2020) - Yoshihara, Hikari A.I.; Bastiaansen, Jessica A.M.; Karlsson, Magnus; Lerche, Mathilde H.; Comment, Arnaud; Schwitter, Juerg
Abstract : Under normal conditions, the heart mainly relies on fatty acid oxidation to meet its energy needs. Changes in myocardial fuel preference are noted in the diseased and failing heart. The magnetic resonance signal enhancement provided by spin hyperpolarization allows the metabolism of substrates labeled with carbon‐13 to be followed in real time in vivo. Although the low water solubility of long‐chain fatty acids abrogates their hyperpolarization by dissolution dynamic nuclear polarization, medium‐chain fatty acids have sufficient solubility to be efficiently polarized and dissolved. In this study, we investigated the applicability of hyperpolarized [1– 13 C]octanoate to measure myocardial medium‐chain fatty acid metabolism in vivo. Scanning rats infused with a bolus of hyperpolarized [1– 13 C]octanoate, the primary metabolite observed in the heart was identified as [1– 13 C]acetylcarnitine. Additionally, [5‐ 13 C]glutamate and [5‐ 13 C]citrate could be respectively resolved in seven and five of 31 experiments, demonstrating the incorporation of oxidation products of octanoate into the tricarboxylic acid cycle. A variable drop in blood pressure was observed immediately following the bolus injection, and this drop correlated with a decrease in normalized acetylcarnitine signal (acetylcarnitine/octanoate). Increasing the delay before infusion moderated the decrease in blood pressure, which was attributed to the presence of residual gas bubbles in the octanoate solution. No significant difference in normalized acetylcarnitine signal was apparent between fed and 12‐hour fasted rats. Compared with a solution in buffer, the longitudinal relaxation of [1– 13 C]octanoate was accelerated 3‐fold in blood and by the addition of serum albumin. These results demonstrate the potential of hyperpolarized [1– 13 C]octanoate to probe myocardial medium‐chain fatty acid metabolism as well as some of the limitations that may accompany its use. Abstract : Fatty acids are normally the main energy source of the heart, and changes in myocardial fuel preference are associated with disease. Here, we investigated the applicability of hyperpolarized [1– 13 C]octanoate as a probe of myocardial medium‐chain fatty acid metabolism. Scanning rats infused with a bolus of hyperpolarized [1– 13 C]octanoate shows [1– 13 C]acetylcarnitine to be the main myocardial metabolite, and [5‐ 13 C]glutamate and [5‐ 13 C]citrate could also be resolved in some experiments.